Appropriate Use Of Drug In Skin Disease Patients At Delima Pharmacy, Tegal District - Prabandari, Sari; Susiyarti, Susiyarti; Monica, Monica (Sean Institute, 2023)
Skin disease is one of the most common health problems in society and is a disease that is still very dominant and a public health problem in Indonesia. Treatment of skin diseases depends on the type of cause, so the accuracy of drug use is critical to prevent therapy failure in patients. Therefore, in the proper and rational use of drugs, it is necessary to carry out various activities to guarantee quality, one of which is the prescribing of drug use. The purpose of this study was to analyze the pattern of drug use in skin patients at Delima Pharmacy in terms of patient characteristics, patient diagnoses, and drug treatment received by patients. The research method uses descriptive analysis with qualitative and quantitative approaches. The research was conducted in May 2023. The population in this study was 990 sheets in March 2023 at Delima Pharmacy. The sample used in this study was 91 prescription sheets by the Slovin method, and the selection was made using the purposive sampling method, which met the inclusion and exclusion criteria. Furthermore, the interview method was carried out with the pharmacist in charge of the pharmacy and pharmaceutical technical staff working at the Delima Pharmacy location to explore more about drug use in patients using skin disease drugs at the Pomegranate pharmacy by providing drugs based on the diagnosis given by the doctor. The classification of drugs is based on therapeutic class, namely antibiotics, antihistamines, antifungals, corticosteroids, anti-inflammatories, and vitamins. Preparations used in the treatment are orally and topically. The most extensive use is topical, with an anti-inflammatory therapy class of 21.94%.